Chemical defence in the red-billed wood hoopoe : phoeniculus purpureus - Law-Brown, Janette (Department of Biological Sciences, 2014)
Red-billed Woodhoopoes, Phoeniculus purpureus, produce a pungent smelling secretion from their uropygial gland. Previous researchers have noted this odour and there has been much speculation on its function. This encouraged me to undertake this study to determine the origin of the odour and the role that the secretion plays. The chemical analysis of this secretion shows that it consists of 17 compounds including acids, aldehydes, lactones and other miscellaneous compounds. Cultures of the secretion showed the presence of a symbiotic bacterium resident within the gland. Antibiotic treatment of the gland suggested that this bacterium was instrumental in the synthesis of the secretion of P. purpureus. This bacterium has not previously been identified and has been proposed as 'Enterococcus phoeniculicola' (GenBank accession number: AYO28437). The secretion was synthesized and the responses of a range of 13 pathogenic and one parasitic bacteria were tested against it and its individual constituent compounds. The synthetic secretion and seven of its constituent compounds inhibited the growth of these bacteria. However, exposing feather mites resident upon the birds to the synthetic secretion did not illicit any significant response from these mites. Wanless (1998) showed that the synthetic secretion causes an averse reaction in cats. In this study I was able to identify indole, phenol and propionaldehyde as being responsible for eliciting this reaction in cats. A similar averse reaction is shown by Rock Monitor Lizards, Varanus albigularis, upon encountering mice tainted with the synthetic secretion. This is the first demonstration of a symbiotic relationship between birds and bacteria in which the modification of the birds' uropygial oils affords the birds some protection against pathogens and preators.